Parents with Fetal Alcohol Spectrum Disorders in the child protection systems: Issues for parenting capacity assessments - Choate, Peter (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
Parents who have or are thought to have Fetal Alcohol Spectrum Disorder (FASD) are often involved in the child protection systems, although there is little data to establish actual frequency. First Nations parents are over represented. There is often a presumptive bias that individuals with disabilities, including FASD, are not capable of raising their children. Such a bias is unwarranted. Assessing FASD parents requires a view of functional capacity along with consideration of how the parent could accomplish the role and if needed, with what supports. Both a context and process for Parenting Capacity Assessments (PCAs) in these cases is recommended. There is a need for the assessments to exist within a cultural context, including the use of the Medicine Wheel. The individualistic perspective of most Canadian child welfare systems may not match the collectivistic approach to parenting in an Aboriginal family system although it is from the former position that most PCAs are conducted.